RME application and its effectiveness in learning mathematics to improve students critical thinking skills - Sukarma, I Ketut (PT. Anagata Sembagi Education, 2024)
This research aims to analyze the application of the Realistic Mathematics Education (RME) approach in enhancing students' critical thinking abilities in mathematics learning. The study uses a quantitative design with a survey method, involving 150 respondents who are secondary school students. Data were collected through a questionnaire measuring two main variables: the implementation of RME and critical thinking abilities. The data analysis results indicate that the application of the RME approach significantly impacts the improvement of students' critical thinking abilities, with a p-value < 0.05. Based on simple linear regression analysis, the R² value of 75% was obtained, showing that 75% of the variation in critical thinking ability can be explained by the application of RME. This study suggests that RME can be an effective alternative to enhance students' critical thinking skills in mathematics learning.